The Matheny Manifesto : a young manager's old school views on success in sports and life - Matheny, Mike, 1970-; Jenkins, Jerry B. (Crown Archetype, 2015)
Mike Matheny was just forty-one when he succeeded the legendary Tony La Russa as manger of the St. Louis Cardinals in 2012. He enjoyed immediate success as a manager, leading the Cards to the postseason three times in his first three years. But he is perhaps as well known for his tough-love philosophy, famously expressed in a frankly worded letter he wrote to the parents of a Little League team he coached. That letter contained his throwback beliefs that authority should be respected, discipline and hard work rewarded, spiritual faith cultivated, family made a priority, and humility considered a virtue. In The Matheny Manifesto, he builds on his original letter by first diagnosing the problem at the heart of youth sports and then offering a hopeful path forward.